2010
DOI: 10.1021/bi100825z
|View full text |Cite
|
Sign up to set email alerts
|

Pnc1p Supports Increases in Cellular NAD(H) Levels in Response to Internal or External Oxidative Stress

Abstract: Following transfer from medium with fermentable glucose to medium with non-fermentable acetate as the carbon source, cellular levels of NAD(H) were found to increase ~two-fold in a parental yeast strain. Similar transfer of a mutant strain subject to endogenous oxidative stress under these conditions produced more dramatic increases in cellular levels of NAD(H), and elevations above parental levels were shown to be due to the nicotinimidase Pnc1p. Similar transient increases in NAD(H) levels observed in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This suggests that a mechanism for inducible cross talk may exist between exogenous and endogenous stimuli. Indeed, exogenous ROS appear to cross talk with endogenous oxidases to activate NF-κB as demonstrated in an NADPH oxidase-deficient mouse model [70]. The magnitudes of the increases in NADPH levels were similar in response to either endogenous or exogenous oxidative stress [71].…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that a mechanism for inducible cross talk may exist between exogenous and endogenous stimuli. Indeed, exogenous ROS appear to cross talk with endogenous oxidases to activate NF-κB as demonstrated in an NADPH oxidase-deficient mouse model [70]. The magnitudes of the increases in NADPH levels were similar in response to either endogenous or exogenous oxidative stress [71].…”
Section: Discussionmentioning
confidence: 97%
“…Nicotinamidase enzymes play a critical role in maintaining NAD + homeostasis and have been found to contribute to important biological processes in both prokaryotes and eukaryotes, including bacterial pathogenesis (Anderson et al , 2003; Balan et al , 2008; Evans et al , 2010; Frothingham et al , 1996; Ghislain et al , 2002; Hunt et al , 2007; Kim et al , 2004; Minard & McAlister-Henn, 2010; Purser et al , 2003; Raynaud et al , 1998; Silva et al , 2009; van der Horst et al , 2007; Vrablik et al , 2009; Wang & Pichersky, 2007). Because of the absence of nicotinamidases in mammals, these enzymes may be potential drug targets for mammalian pathogens (Sauve, 2008), including the Lyme disease spirochaete B. burgdorferi .…”
Section: Discussionmentioning
confidence: 99%
“…This could be a cellular response to the state of constitutive oxidative stress in mutant cells. Two studies reported that treatment of wild-type cells with H 2 O 2 induced an increase in total NAD + + NADH levels [28,29]. In addition, the salvage pathway appears to be necessary for this increase under oxidative stress conditions [29].…”
Section: Nad + /Nadh Pools In Yfh1 and Aat1 Cellsmentioning
confidence: 99%